Chapter Gli "Ammaestramenti degli Antichi"di Bartolomeo da San Concordio. Prime osservazioni in vista dell'edizione critica - CONTE, MARIA (Reti Medievali E-Book, 2020)
Bartholomew of San Concordio translated his Documenta antiquorum into the vernacular presumably around 1297-1302, during his stay at the convent of Santa Maria Novella. Cesare Segre suggested such a date based on the dedication of the translation to Geri Spini, a Florentine banker and politician who was a supporter of the Black Guelfs and a close friend of Corso Donati. However, the relationships between the Dominican Friar and the Commune of Florence, as well as the potential connections between Bartholomew's self-translation and Florentine political contingencies, are still to be investigated.